2015
DOI: 10.1152/ajpendo.00151.2015
|View full text |Cite
|
Sign up to set email alerts
|

Nε-(carboxymethyl) lysine-induced mitochondrial fission and mitophagy cause decreased insulin secretion from β-cells

Abstract: Lo MC, Chen MH, Lee WS, Lu CI, Chang CR, Kao SH, Lee HM. N ε -(carboxymethyl) lysine-induced mitochondrial fission and mitophagy cause decreased insulin secretion from ␤-cells. Am J Physiol Endocrinol Metab 309: E829 -E839, 2015. First published September 22, 2015; doi:10.1152/ajpendo.00151.2015 ε -(carboxymethyl) lysine-conjugated bovine serum albumin (CML-BSA) is a major component of advanced glycation end products (AGEs). We hypothesised that AGEs reduce insulin secretion from pancreatic ␤-cells by damaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 40 publications
3
20
0
1
Order By: Relevance
“…In addition, lysine acetylation was also previously reported to affect both immunological and metabolic pathways, which could then induce type II diabetes and cardiovascular disease (Iyer & Fairlie, ; Kosanam et al, ). Nε‐(carboxymethyl) lysine‐conjugated bovine serum albumin is an essential component of advanced glycation end products which could damage mitochondrial functions and result in reducing insulin secretion followed by the incidence of diabetes (Lo et al, ). Diabetes could control many aspects of endocrine, including steroidogenesis, whose perturbation could in turn induce the initiation of diabetes (Hwang, ; Jangir, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lysine acetylation was also previously reported to affect both immunological and metabolic pathways, which could then induce type II diabetes and cardiovascular disease (Iyer & Fairlie, ; Kosanam et al, ). Nε‐(carboxymethyl) lysine‐conjugated bovine serum albumin is an essential component of advanced glycation end products which could damage mitochondrial functions and result in reducing insulin secretion followed by the incidence of diabetes (Lo et al, ). Diabetes could control many aspects of endocrine, including steroidogenesis, whose perturbation could in turn induce the initiation of diabetes (Hwang, ; Jangir, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that AGE injections can initiate β -cell dysfunction in vivo [25]. A recent in vitro study also indicated that CML caused mitochondrial dysfunction and mitophagy in β -cells and that high levels of AGEs may induce β -cell dysfunction and impair insulin secretion ability [26]. A recent epidemiological study also showed that increased fasting CML levels may be predictive of type 2 diabetes development [27].…”
Section: Discussionmentioning
confidence: 99%
“…The insulin resistant mice (beta-cell-specific Atg7 knockout mice) model has been shown that autophagy plays a crucial role in the development of diabetes and in preserving the structure and function of pancreatic beta cells. Accumulation of autophagosomes in the pancreatic beta cell has been demonstrated in db/db mouse model [134136]. Fujitani et al showed that reduced insulin secretion was associated with pancreatic beta cell degeneration and impaired glucose in autophagy-deficient mice [136138].…”
Section: Autophagy and Type 2 Diabetes (T2d)mentioning
confidence: 99%